FÍSICA PARA TODOS: A CONSTRUÇÃO DE UMA RODA D’ÁGUA - Frizzo, Leonardo Armando; Kürschner, Victor Noster; Schonardie, Mateus Felzke; Toniazzo, Nelson Adelar; Schmidt, Pedro Afonso (Salão do Conhecimento, 2019)
Projeto de extensão do projeto Física para todos